Poziom akceptacji dla feminatywów wśród osób studiujących i pracujących na UAM. Kontekst płci i statusu na uczelni - Zachorska, Martyna F.; Klon, Weronika; Waszyńska, Katarzyna (Studia Edukacyjne, 2024)
The purpose of the project was to investigate the level of acceptance of feminine forms of job titles (feminitives) in the academic community of Adam Mickiewicz University in Poznan (The context of gender and university status). The survey was conducted using the Qualtrix platform. The names of professions were selected from the alphabetical index of professions and specialties (2014). Ultimately, 102 occupation names and 11 function names were used in the survey. The respondents were told to define their own level of acceptance of each feminine form on a six-point scale from 0 to 5. The research group consisted of full-time students and academic staff (364 people) working at Adam Mickiewicz University, Poznań.